Novel Tautomerisation Mechanisms of the Biologically Important Conformers of the Reverse Löwdin, Hoogsteen, and Reverse Hoogsteen G*·C* DNA Base Pairs via Proton Transfer: A Quantum-Mechanical Survey - Brovarets', Ol'ha O.; Oliynyk, Timothy A.; Hovorun, Dmytro M. (Frontiers in Chemistry, 2019)
For the first time, in this study with the use of QM/QTAIM methods we have exhaustively investigated the tautomerization of the biologically-important conformers of the G*∙C* DNA base pair – reverse Löwdin G*∙C*(rWC), Hoogsteen G*´∙C*(H) and reverse Hoogsteen G*´∙C*(rH) DNA base pairs – via the single (SPT) or double (DPT) proton transfer along the neighboring intermolecular H-bonds. These tautomeric reactions finally lead to the formation of the novel G·C*O2(rWC), G*N2·C(rWC), G*´N2·C(rWC), G*N7·C(H) and G*´N7·C(rH) DNA base mispairs. Gibbs free energies of activation for these reactions are within the range 3.64 – 31.65 kcal∙mol-1 in vacuum under normal conditions. All TSs are planar structures (Сs symmetry) with a single exception – the essentially non-planar transition state TSG*·C*(rWC)↔G+·C-(rWC) (С1 symmetry). Analysis of the kinetic parameters of the considered tautomerization reactions indicates that in reality only the reverse Hoogsteen G*´·C*(rH) base pair undergoes tautomerization. However, the population of its tautomerised state G*´N7·C(rH) amounts to an insignificant value – 2.3·10-17. So, the G*∙C*(rWC), G*´∙C*(H) and G*´∙C*(rH) base pairs possess a permanent tautomeric status, which does not depend on proton mobility along the neighboring H-bonds. The investigated tautomerization processes were analyzed in details by applying the author’s unique methodology – sweeps of the main physical and chemical parameters along the intrinsic reaction coordinate. In general, the obtained data demonstrate the tautomeric mobility and diversity of the G*∙C* DNA base pair.